2013
DOI: 10.1155/2013/403717
|View full text |Cite
|
Sign up to set email alerts
|

Living with Uncertainty: Older Persons’ Lived Experience of Making Independent Decisions over Time

Abstract: The aim of the study was to illuminate the meaning of older persons' independent decision making concerning their daily care. Autonomy when in care is highly valued in the western world. However, research shows that autonomy can give rise to problematic issues. The complexity of independence and dependence for older people when living at home with help has also been highlighted. In Sweden, older people are increasingly expected to live at home with help from municipal home care services, and study into this as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 20 publications
4
37
0
Order By: Relevance
“…Twelve articles (Ek et al, 2011;Liveng, 2011;Breitholtz et al, 2012Breitholtz et al, , 2013aByrne et al, 2012;Doyle, 2012;Holmberg et al, 2012;Swedberg et al, 2012;Witsø et al, 2012;Glasdam et al, 2013;Moe et al, 2013;Hillcoat-Nall etamby, 2014) are included and distributed across the following nationalities: Sweden (5) Norway (2) Denmark (2) Canada (1) Wales (UK) (1) Australia (1). All countries have home care and legislation which respects people 0 s right to self-determination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve articles (Ek et al, 2011;Liveng, 2011;Breitholtz et al, 2012Breitholtz et al, , 2013aByrne et al, 2012;Doyle, 2012;Holmberg et al, 2012;Swedberg et al, 2012;Witsø et al, 2012;Glasdam et al, 2013;Moe et al, 2013;Hillcoat-Nall etamby, 2014) are included and distributed across the following nationalities: Sweden (5) Norway (2) Denmark (2) Canada (1) Wales (UK) (1) Australia (1). All countries have home care and legislation which respects people 0 s right to self-determination.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between the carer and the older person is crucial when it comes to the ability to make autonomous decisions. The studies depict the carer's approach to the relationship as the key factor in letting the older person 0 s autonomy be expressed (Ek et al, 2011;Liveng, 2011;Breitholtz et al, 2012Breitholtz et al, , 2013aByrne et al, 2012;Doyle, 2012;Holmberg et al, 2012;Swedberg et al, 2012;Moe et al, 2013). The analysis shows a large spread in the older person 0 s perceptions of care.…”
Section: Autonomy and Relationshipmentioning
confidence: 99%
“…Hearle, Prince, and Rees () and Nicholson, Meyer, Flatley, Holman, and Lowton () describe that transitions between being independent and becoming dependent on others often imply a sense of helplessness and reduced well‐being. On the other hand, Breitholtz, Snellman, and Fagerberg () found that older people with home care still see themselves as being as independent as they were when they were young, and they view caregivers as an extension of themselves. Moreover, de Jonge, Jones, Phillips, and Chung () noted that older people enjoy the independence and autonomy afforded by living in their own home; thus, home care is associated with both positive and negative experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Breitholtz et al. () add that decision‐making is not a simple undertaking; it requires a constant balance, which can be difficult. From a caregiver's perspective, respect for the right of self‐determination means so much more than just surrendering control.…”
Section: Discussionmentioning
confidence: 99%
“…Information about a disease may decrease insecurity and increase feelings of control,39 and help seniors with multimorbidity to cope with the consequences of diseases 40. Caregivers need to acknowledge that seniors’ life situations involve living with uncertainty over time 41. Previously, seniors (>75 years old) reported poor understanding of their health and diseases 17.…”
Section: Discussionmentioning
confidence: 99%